Mikroenkapsulasi Likopen dari Buah Tomat dengan Metode Penguapan Pelarut: Microencapsulation of Lycopene from Tomato Fruit by Solvent Evaporation Method - Sulastri, Evi; Ibrahim, Nurlina; Budiarti, Suci (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2019)
Lycopene is a carotenoid group easily damaged due to the oxidation process (light, oxygen and temperature) and isomerization during storage. This damage can be minimized by microencapsulation processes. The objective of this study was to develop novel microencapsulation of lycopene extracts from tomato fruit by solvent evaporation method using ethyl cellulose as wall materials and to select the optimum formulation. Three microcapsule formulations were prepared containing the ratio of lycopene and ethyl cellulose (L:ES) of 1:1, 1:2 and 1:3. The morphology of the microcapsules was analysed by optical microscopy and scanning electronic microscopy. The encapsulation efficiency, particle size, recovery yield and moisture content were also examined. The result showed that all microcapsule formula were aggregated and irregular in shape with encapsulation efficiency of 6.13- 19.43%, moisture content of 1,63- 7,52%, recovery yield of 81-98,12% and particle size of 46,2-86Âµm. Microcapsule with a ratio 1:3 (L:ES) was the most optimum formula based on a maximum encapsulation efficiency than the others